Akidah Islam dan Teologi Multikultural: Strategi Pendidikan Agama Islam untuk Membentuk Karakter Moderat Generasi Z - Adzibah, Salsabila I'tilaful; Adzillah, Salsabila Nur Imatul; Arif, Mahmud (Arfannur: Journal of Islamic Education, 2025)
This study aims to examine the meaning of Islamic creed (ʿaqīdah) within the framework of multicultural theology and explore its integration into Islamic Religious Education (IRE) strategies to shape moderate character among Generation Z. The research employed a descriptive qualitative approach through library research, enabling a critical analysis of academic literature, policy documents, and curriculum frameworks. The findings reveal that Islamic creed, when interpreted inclusively through the lens of multicultural theology, functions not only as a spiritual foundation but also as a social ethic that nurtures the values of tolerance (tasāmuh), equality (musāwah), justice (taʿādul), and compassion (raḥmah). Contextual, participatory, and experience-based IRE strategies prove to be highly relevant for Generation Z, who are critical, adaptive, and digitally literate. The implications highlight the crucial role of curriculum development, pedagogical innovation, and teacher competence in delivering transformative religious education that simultaneously prevents radicalization. However, the study acknowledges its conceptual limitations, emphasizing the need for further empirical and comparative research to test the effectiveness of the proposed strategies across diverse educational and social settings. Accordingly, this study offers both theoretical and practical contributions to strengthening religious moderation among Generation Z in alignment with the vision of Islam as raḥmatan lil-ʿālamīn